Análise da transição da carreira esportiva de atletas de futebol da fase amadora para a fase profissional - Mauricio Pimenta Marques (2008)
The sports career of an athlete has various phases from initiation to retirement. Researchabout these phases and their transitions has focused mainly on career termination while veryfew studies have been done on other important transitions. Considering the social and culturalcontext of football in Brazil, this study analyzes the career of athletes in early adulthood thatare facing the transition between amateur to professional sport. The aims of this study were:(a) identify relevant factors in the sport initiation phase of the athletes (b) characterize theirfamily and social context; (c) identify factors that interfere in their career planning actions; (d)analyze their perception about the football context in which they are inserted. A sample of186 athletes with an average age of 18,46 years old (± 0,82) participated of the study. Amixed qualitative and quantitative method approach was used with two instruments for datacollection: (1) a 46 question questionnaire based on the Athletic and Post-athleticQuestionnaire and the Sports Career Transitions and (2) a semi structured interview. Theresults showed that the sports initiation of these athletes happen on the streets and in footballacademies afterwards. Regarding the type of practice, futsal (indoor football) was identifiedas a common practice; however, these athletes have not practiced a variety of sports in thisphase as indicated in studies conducted with talented children form developed countries. Thestudy has found that the majority of the players families lie at lower social economic levels,but a significant number of medium class families appear to be now providing support fortheir children to become professional football players. The social relationships of theseplayers have undergone huge changes along their careers and what they miss most nowadaysis to go out with friends and girlfriends. The athletes have shown a reasonable level ofprevious career planning, except for issues related to studies. The father is the main counselorof most of the athletes, while the manager appears to have an increasing influence on theircareer. The perception of the athletes about the football context is very positive, even thoughthey still face a number of problems. It seems that the dream of becoming a professionalfootball player overcomes any difficulty. The study also identified that what they enjoy mostin football is traveling, personal satisfaction and the competitive environment. The biggestproblems are school, distance from the family and injuries. Their perception is that the mainsupport comes from the family.